Characterization and catalytic behavior of hydrotalcite-derived Ni–Al catalysts for methane decomposition. (10th July 2020) - Shi, Zemin; Wan, Chunsheng; Huang, Min; Pan, Jinhua; Luo, Ruizhi; Li, Dalin; Jiang, Lilong
Abstract: A series of Ni catalysts were prepared from Ni–Al hydrotalcite-like compounds (HTlcs) by varying the Ni/Al molar ratio (1–4) and calcination temperature (773–1173 K) of HTlcs. The catalysts were reduced with H2 at 1073 K and tested for CH4 decomposition at 773–923 K on a thermal gravimeter. Various techniques including N2 physical adsorption, XRD, H2 -TPR, XPS, HAADF-STEM, TEM, and Raman were applied to characterize the catalysts and the as-produced carbon. The characterizations show that calcination of Ni–Al HTlcs leads to Ni(Al)O solid solution and minor NiO and/or NiAl2 O4 spinel may be formed depending on the Ni/Al ratio and calcination temperature; upon reduction at 1073 K, most nickel species are reduced to metallic Ni. In CH4 decomposition, carbon yield shows a volcano-type dependence on the Ni content with the optimum Ni/Al ratio equal to 3. On the other hand, carbon yield is affected by the calcination temperature of the Ni3 Al HTlcs to a small extent. Carbon yield is also significantly affected by the reaction temperature, which decreases remarkably with a rise of temperature to 923 K. TEM and Raman indicate that fish-bone carbon nanofibers are formed at 773–823 K, whereas multi-walled carbon nanotubes are formed at 873–923 K. Highlights: Calcination of Ni–Al HTlcs gives Ni(Al)O solid solution as the main product. Nickel species are almost completely reduced to metallic Ni at 1073 K. Carbon yield in CH4 decomposition shows a volcano-type dependence on the Ni content. The Ni3 Al catalyst calcined at 1073 K shows better catalytic performance. Carbon nanofibers and nanotubes are formed at below and above 873 K, respectively.